The Effectiveness of implementation of standard clinical pathway through healthcare professionals among acute myocardial infarction patients undergoing for angiography / angioplasty in a public tertiary care hospital, Karachi - Shahzad Bashir; Sarfraz Masih; Rubina Barolia; Muhammad Nawaz Lashari; Iram Amin (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the effect of acute myocardial infarction standard clinical pathway among acute myocardial infarction patients on length of stay in public tertiary care settings. Methods: The quasi-experimental non-randomised case-control study was conducted at the Department of Cardiology, Dr Ruth Pfau Civil Hospital, Karachi, from September to December 2018, and comprised acute myocardial infarction in-patients. Those admitted before the implementation of acute myocardial infarction standard clinical pathway formed the control group, while those admitted after the implementation were in the intervention group. Acute myocardial infarction standard clinical pathway was implemented and the interventional clinical practices of healthcare professionals, including cardiologists, postgraduates, residents, nurses and critical care technicians, were assessed using a standard checklist. Data was analysed using SPSS 21. Results: Of the 100 participants, 50(50%) were in the control group; 31(62%) males and 19(38%) females. The intervention group also had 50(50%) patients; 35(70%) males and 15(30%) females. Regarding effectiveness of the implementation of standard clinical pathway, length of hospital stays reduced significantly in the intervention group compared to the control group (p=0.003). Conclusion: The implementation of acute myocardial infarction standard clinical pathway reduced the length of hospital stay of acute myocardial infarction in- patients. Key Words: Acute Myocardial Infarction, AMI standard clinical pathway, Length of hospital stay, LOS, Angiography, Angioplasty, Health care professionals. Continue...